TINDAK PIDANA PEMERASAN YANG BERUJUNG PADA PEMBUNUHAN ANALISIS YURIDIS DALAM PERSPEKTIF HUKUM PIDANA INDONESIA - Ronny Erlando; Siti Humulhaer; Dian Retno Widayati; Teddy T Pingak; Nida Lailatu Syabani; Al Bukhori (CV. Lafadz Jaya, 2026)
The criminal act of extortion that results in murder is a complex criminal phenomenon that requires in-depth analysis from the perspective of Indonesian criminal law. This study aims to analyze the criminal liability of perpetrators of extortion that results in the death of the victim, as well as to examine the relevant juridical aspects in handling such cases. The research method used is a normative-empirical legal research method with a case approach. The results of the study indicate that the criminal act of extortion leading to murder is regulated under Article 368 paragraph (2) in conjunction with Article 365 paragraphs (3) and (4) of the Indonesian Criminal Code, with a maximum imprisonment penalty of up to 15 years and even the death penalty under certain circumstances. This study recommends the need for consistent law enforcement and the harmonization of statutory regulations in order to provide maximum protection for victims.